Analisis Pengaruh Variety Seeking, Status Sosial, Kualitas Produk, dan Iklan Terhadap Perpindahan Merek (Brand Switching): Studi pada Pengguna Smartphone Iphone yang Sebelumnya Pernah Menggunakan Merek Lain di Yogyakarta dan Sekitarnya - Mekar Ayu Cahyaningtyas (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the effect of Variety Seeking, social status, product quality, and advertising on brand switching among iPhone smartphone users who have previously used other brands in Yogyakarta and its surroundings. The variables used in this study are independent variables consisting of Variety Seeking, social status, product quality, and advertising, while the dependent variable in this study is Brand Switching. The type of data in this study is primary data which is the answer from 100 respondents. The method used in this study is non-probability sampling and with accidental sampling technique. This type of quantitative research uses a survey method. The analysis tool in this study uses Multiple Linear Regression Analysis. (1) The results of this study indicate that there is a positive and significant joint influence of Variety Seeking, social status, product quality, and advertising on brand switching. (2) The variables Variety Seeking, social status, and product quality have a positive and significant effect on brand switching. However, the Advertising Variable does not affect brand switching among iPhone smartphone users who have previously used other brands in Yogyakarta and its surroundings.